Comparison of Education Policy Through Approaches to Character Education in Indonesia and Japan - Astri Nurfauziah; Deni Darmawan; Buiyeva Kibrio Ergashevna (CV. Ksatria Siliwangi, 2024)
This study aims to compare character education policies in Indonesia and Japan through a descriptive qualitative approach. Character education is an important element in the formation of a moral and responsible generation. In Indonesia, character education is integrated into the curriculum based on Pancasila values, while Japan implements it through moral education (dotoku kyoiku) which is structured and systemic. The results of the study show that although both countries have the same goal in shaping the character of students, the approach and implementation are different. Japan stands out in the consistency and integration of moral values in all aspects of school life, while Indonesia has strengths in local values but faces challenges in implementation at the practical level. This study recommends strengthening teacher training and integrating school culture in character education in Indonesia.